2016
DOI: 10.1108/ijopm-05-2015-0265
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of internal manufacturing network integration

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 86 publications
1
44
0
1
Order By: Relevance
“…fully mediate the relationship between network globalization and a plant's sustainable development.Fourth, we analyzed whether a plant's collaborative integration with sister facilities could support the adoption of novel sustainable practices. While previous IMSS-based studies found a positive relationship between manufacturing network integration and operational performance (e.g Szász et al, 2016),. its effect over the adoption of sustainable production and sourcing is new to the Operations Strategy literature.…”
mentioning
confidence: 87%
“…fully mediate the relationship between network globalization and a plant's sustainable development.Fourth, we analyzed whether a plant's collaborative integration with sister facilities could support the adoption of novel sustainable practices. While previous IMSS-based studies found a positive relationship between manufacturing network integration and operational performance (e.g Szász et al, 2016),. its effect over the adoption of sustainable production and sourcing is new to the Operations Strategy literature.…”
mentioning
confidence: 87%
“…Country-level economic development has a direct negative effect on quality ( =−0.124; p<0.001) and delivery ( =−0.150; p<0.001), but no significant effect on flexibility and cost efficiency. These results are consistent with Schoenherr (2012) and Szasz et al (2016), among others. This might occur because developed countries attain higher levels of effectiveness and, therefore, their direct effects are less evident than in countries that have lower levels of performance (Meijboom and Vos, 1997;Gupta and Govindarajan, 2000;Ambos et al, 2006;Szasz et al, 2016 (Landsom, 2000;Da Silveira and Sousa, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Some authors use the same year to compare practices and performance (e.g. Gimenez et al, 2012;Szasz et al, 2016) but, as aforementioned, the benefits of sustainability practices might only appear years later. Second, sustainability management includes a wide range of practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations